Genetically predicted vitamin C levels significantly affect patient survival and immunotypes in multiple cancer types - Yuan, Jing; Zhang, Yu-hong; Hua, Xin; Hong, Hui-qi; Shi, Wei; Liu, Kun-xiang; Liu, Ze-xian; Huang, Peng (Frontiers in Immunology, 2023)
Background Recent observational studies and meta-analyses have shown that vitamin C reduces cancer incidence and mortality, but the underlying mechanisms remain unclear. We conducted a comprehensive pan-cancer analysis and biological validation in clinical samples and animal tumor xenografts to understand its prognostic value and association with immune characteristics in various cancers. Methods We used the Cancer Genome Atlas gene expression data involving 5769 patients and 20 cancer types. Vitamin C index (VCI) was calculated using the expression of 11 genes known to genetically predict vitamin C levels, which were classified into high and low subgroups. The correlation between VCI and patient overall survival (OS), tumor mutational burden (TMB), microsatellite instability (MSI), and immune microenvironment was evaluated, using Kaplan-Meier analysis method and ESTIMATE (https://bioinformatics.mdanderson.org/estimate/). Clinical samples of breast cancer and normal tissues were used to validate the expression of VCI-related genes, and animal experiments were conducted to test the impact of vitamin C on colon cancer growth and immune cell infiltration. Results Significant changes in expression of VCI-predicted genes were observed in multiple cancer types, especially in breast cancer. There was a correlation of VCI with prognosis in all samples (adjusted hazard ratio [AHR] = 0.87; 95% confidence interval [CI] = 0.78–0.98; P = 0.02). The specific cancer types that exhibited significant correlation between VCI and OS included breast cancer (AHR = 0.14; 95% CI = 0.05–0.40; P < 0.01), head and neck squamous cell carcinoma (AHR = 0.20; 95% CI = 0.07–0.59; P < 0.01), kidney clear cell carcinoma (AHR = 0.66; 95% CI = 0.48–0.92; P = 0.01), and rectum adenocarcinoma (AHR = 0.01; 95% CI = 0.001–0.38; P = 0.02). Interestingly, VCI was correlated with altered immunotypes and associated with TMB and MSI negatively in colon and rectal adenocarcinoma (P < 0.001) but positively in lung squamous cell carcinoma (P < 0.05). In vivo study using mice bearing colon cancer xenografts demonstrated that vitamin C could inhibit tumor growth with significant impact on immune cell infiltration. Conclusion VCI is significantly correlated with OS and immunotypes in multiple cancers, and vitamin C might have therapeutic potential in colon cancer.